Northern Ghana communities farmer profiles on agronomy and crop insurance advisories - Kizito, Fred (2021)
This dataset is about the Northern Ghana Communities Farmer Profiles on Agronomy and Crop insurance advisories. In order to increase productivity at farmer and community levels, the Excellence in Agronomy 2030 Initiative (EiA) in partnership with WorldCover is investigating how best to characterize, boost and scale out promising agronomic options through cropping advisory services in Northern Ghana. These options include a suite of interventions such as the use of high yielding quality seeds, use of improved fertilizers, use of organic manure and soil and water conservation measures within smallholder farming systems while also emphasizing the inclusivity of women and considering gender dimensions. This dataset provides beneficiary farmer profiles (both male and female) in relation to demographic characteristics, documents their current farming practices and assesses their knowledge levels in the context of crop insurance, level of access to information as well as elicits dynamics around input and output markets and services. The project team will Interview associated beneficiaries and non-beneficiaries. (2021-01-13)